Consumer Preferences on Processed Herbs and Spices Products of SMEs in Sukoharjo - Suryaningrum, Dyah Ayu Suryaningrum; Rizki Puspita Dewanti; Rysca Indreswari; Ina Marwantina (Jurnal Informasi dan Teknologi, 2024)
The demand for herbs and spices products in Indonesia has been steadily increasing each year, especially since the pandemic of COVID-19 pandemic. Information from various media about the benefits of herbs and spices for maintaining health and body stamina has encouraged people to consume the products and their derivations forms. The emergence of various processed herbs and spices products requires producers to better understand consumer behavior. This research aims to understand the decision-making process of purchasing and consumer preferences for processed spice and herbal products produced by SMEs (Micro, Small, and Medium Enterprises) in Sukoharjo Regency. The research involved 103 respondents from Sukoharjo Regency who have consumed herbs and spices products made by SMEs during the last three months. Descriptive methods were conducted through direct interviews with consumers using questionnaires, while conjoint analysis was used to determine the attributes most considered by consumers when making a purchase. The research findings show that the characteristics of consumers of processed herbs and spices products in Sukoharjo Regency are generally dominated by females, aged 17 to 25 years, mainly students, with a monthly income of around IDR 2,000,000. There are three main attributes considered when selecting products, namely taste (23,2%), sugar content (19,1%), and serving forms (12,4%), while the brand attribute has the lowest importance value at 9.4%.